A mobile health technology intervention for addressing the critical public health issue of child mortality. Issue 1 (21st December 2017) - O'Connor, Yvonne; O'Sullivan, Timothy; Gallagher, Joseph; Heavin, Ciara; Hardy, Victoria; O'Donoghue, John
Abstract: Evaluations of development initiatives in resource‐poor settings dominate Health Information Technology/Systems research. Yet a dearth of research exists, which documents the design and development of these technological artefacts. Through the lens of Transition Management Framework, this research attempts to address this gap in literature, to describe a particular technology (ie, Supporting LIFE—SL eCCM App) and the way in which its hardware, software, and system configurations interact with the sociocultural and economic context in one rural region of the Malawian community. This study uses a design science perspective to ensure the design and development of a health technology intervention that is relevant and has utility in the context for which it has been built, ie, Malawi Africa. This paper addresses the manner in which the configurations of a mobile Health intervention (known as Supporting LIFE eCCM App) interact within a developing world context. Supporting LIFE eCCM aims to leverage the critical societal issue of reducing child mortality in Malawi, Africa. The design science approach supports the design and build of a health intervention that is a good fit for the "real‐world" health scenario considered. Coupled with Geel's Transition Management Framework, we emphasise the need for a balanced sociotechnical approach to mHealth, placing individuals at the centre of the IT development project while also considering social, economic, and cultural factors. These are key environmental aspects of a development project such as this one.